Review of literature on agricultural productivity, social capital and food security in Nigeria - Liverpool-Tasie, Lenis Saweda; Kuku, Oluyemisi; Ajibola, Akeem (International Food Policy Research Institute, 2011)
Despite the rapid pace of urbanization taking place in Nigeria, half of Nigerians (approximately 70 million individuals) still live in rural areas; most of them engaged in smallholder semi-subsistence agriculture. Agriculture remains a crucial sector in the Nigerian economy, being a major source of raw materials, food and foreign exchange; employing over 70 percent of the Nigerian labor force, and serving as a potential vehicle for diversifying the Nigerian economy. However, there are no rigorous studies that explain productivity in this sector vis-a-vis the relationship of the sector to food security and social capital. This review assesses the nature and scope of agricultural productivity, food security, and social capital in Nigeria, while also laying the groundwork for investigating the interrelationships among them. The literature reveals the pervasive inefficiency of Nigerian farmers as most smallholder farmers produce significantly below their production frontiers. As a result, they produce less than optimal levels of output as revealed by studies of productivity (mostly land productivity). Also, while many farming enterprises are profitable, profit margins are generally low. The vast majority of Nigerians are reported to be food insecure as revealed by studies on availability, utilization, and access to food. In terms of social capital, most studies are focused on membership in formal or informal organizations or associations, or by the access of individuals or associations to formal and informal sources of credit. Evidence shows that both measures of social capital improve several aspects of social welfare, particularly poverty reduction, in addition to influencing technology adoption. This review also identifies the potential pathways through which all three concepts are linked.